Sweden : 2004 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Sweden. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation highlights that the downturn experienced by the Swedish economy in 2002-03 was relatively mild, with growth remaining well above the European Union average. Expansionary fiscal policy in 2002 underpinned private consumption. Private investment, however, remained weak and activity decelerated when the impact of public sector stimulus waned in the first half of 2003. Economic activity is expected to pick up steadily in 2004-05 as the global recovery gathers pace. Adjusted for calendar effects, output is expected to rise by about 2 percent in 2004.